2010
DOI: 10.1002/ar.21295
|View full text |Cite
|
Sign up to set email alerts
|

A Neurological Comparative Study of the Harp Seal (Pagophilus groenlandicus) and Harbor Porpoise (Phocoena phocoena) Brain

Abstract: The cetacean brain is well studied. However, few comparisons have been done with other marine mammals. In this study, we compared the harp seal (Pagophilus groenlandicus) and the harbor porpoise brain (Phocoena phocoena). Stereological methods were applied to compare three areas of interest: the entire neocortex and two subdivisions of the neocortex, the auditory and visual cortices. The total number of neurons and glial cells in the three regions was estimated. The main results showed that the harbor porpoise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
5
23
1
Order By: Relevance
“…The fact that we could only study 1 specimen of each of the 2 species relates to the very limited availability of toothed whale brain material suitable for stereological investigation. However, our data are consistent within the single cortical areas of our 2 animals (coefficient of error; table 4 ) and they correlate well with data in the literature on the bottlenose dolphin concerning both the total densities of cortical areas (auditory, visual) we investigated and the densities of layers III and V in these cortices [Garey and Leuba, 1986;Morgane et al, 1988, Eriksen andPakkenberg, 2007;Walloe et al, 2010]. We analyzed only cresyl violet-stained sections from the cortex of these 2 animals which were of very good histological quality ( fig.…”
Section: Animalssupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that we could only study 1 specimen of each of the 2 species relates to the very limited availability of toothed whale brain material suitable for stereological investigation. However, our data are consistent within the single cortical areas of our 2 animals (coefficient of error; table 4 ) and they correlate well with data in the literature on the bottlenose dolphin concerning both the total densities of cortical areas (auditory, visual) we investigated and the densities of layers III and V in these cortices [Garey and Leuba, 1986;Morgane et al, 1988, Eriksen andPakkenberg, 2007;Walloe et al, 2010]. We analyzed only cresyl violet-stained sections from the cortex of these 2 animals which were of very good histological quality ( fig.…”
Section: Animalssupporting
confidence: 91%
“…Electrophysiological experiments [Lende and Akdikmen, 1968;Lende and Welker, 1972;Supin, 1970, 1977;Ladygina et al, 1978;Supin et al, 1978Supin et al, , 2001 have shown that near the anteroventral tip of the cerebral hemisphere the motor and somatosensory cortical areas are separated by the cruciate sulcus, presumably a homolog of the central sulcus in primates [Morgane et al, 1980[Morgane et al, , 1986[Morgane et al, , 1990Oelschläger andOelschläger, 2002, 2009]. The auditory field is the largest primary projection area with the highest number of neurons and the largest cortical volume [Walloe et al, 2010; harbor porpoise, Phocoena phocoena ; Eriksen and Pakkenberg, 2007; minke whale, Balaenoptera acutorostrata ]. It is located in the suprasylvian and the posterior ectosylvian gyrus, bordering medially on the visual field which in toothed whales comprises the lateral gyrus adjacent to the interhemispheric cleft ( fig.…”
mentioning
confidence: 99%
“…For example, Herculano-Houzel [129] suggested that even the cerebral cortex of the largest whales might be composed of only a fraction of the average 16,300 million neurons found in the human cerebral cortex. In fact, both Kazu et al [128], and Herculano-Houzel [129] do not agree with the aforementioned results concerning the neuronal numbers found in the cerebral cortex of the harbour porpoise and the minke whale, [3,127] suggesting that the neuron numbers obtained might be over-estimations of the real values due to undersampling problems associated with the stereology quantification technique.…”
Section: Implications For Cetacean Cognitionmentioning
confidence: 93%
“…Furthermore, using stereology quantification techniques [125,126], it was shown that odontocetes such as the long-finned pilot whale (Globicephala melas), or the harbour porpoise (Phocoena phocoena) have an unexpectedly high number of cortical neurons [30,127]. Figures for harbour porpoises approach the lowest cortical neuron number found in humans [104,105], and long-finned pilot whales possessing the highest number of cortical neurons of any species studied so far, including humans [30].…”
Section: Implications For Cetacean Cognitionmentioning
confidence: 99%
See 1 more Smart Citation